The Effectiveness of Active Carbon Adsorbent of Cassava Peel (Manihot Esculenta Cranzts) in Reduce Level of Chromium Metal in Tannery Liquid Waste - Susila Kristianingrum; S. Sulistyani; Annida Rifka Larastuti (Universitas Negeri Yogyakarta, 2022)
This study aims to determine the characteristics, the effect of mass variation, the percentage of adsorption effectiveness of cassava peel activated carbon activated with 0.5 M HCl and activated with 0.5 M H2SO4 on the adsorption of Cr metal in leather tanning wastewater and its morphology. The subject of this research is the adsorbent of cassava peel before it is asctivated, activated by chloric acid 0,5 M, and activated by sulfuric acid 0,5 M. meanwhile the object of this research is the effectiviness of cassava peel adsorbeny in reduscing chromium metal content in tannery liquid waste. Cassava pell was carbonized at 500 oC for 1 hour. The cassava peel carbon was characterized according to SNI 06-3730-1995. The adsorption process is performed by batch method. Analysis was performed by Atomic Adsorption Spectrophotometer, PSA, and SEM-EDX. The result of the characterization of cassava peel carbon showed that the moisture content, ash content, adsorption capacity of I2 met SNI, meanwhile the carbon contenr and volatile matter conten did not met SNI. The adsorption efficiency of kromium metal is 95.97% for carbon before activated, 95.33% for carbon activated by chloroc acid, and 96.65% for carbon activated by sulfuric acid. The result of PSA size of cassava peel adsorbent before activated by chloric acid and sulfuric acid were 34.484 µm, 42.504 µm, and 37.059 µm respectively. Cassave peel adsorbent has a Langmuir adsorption type. The SEM-EDX result showed that the adsorbent from cassava peel had a dissimiliar pore shape